The Effect of Iron Ion to the Removal of Nickel Ion From Electroplating Wastewater Using Double Chamber Electrodeposition Cell (DCEC) Reactor - Djaenudin Djaenudin; Dani Permana (Molekul, 2017)
Modern society demands industrial technology advances to produce products that have high durability and long utilization lives. Materials made from ferrous metal become a solution to meet these industry needs. Ferrous metal is corrosive and it requires more care to support the performance. Electroplating or metal coating applied to iron or nickel solves this problem. In the production process, the usage of nickel is only 30%-40% and the remaining 60-70% is wasted through effluent. Nickel is a toxic heavy metal that can cause cancer. The purpose of this study is to evaluate the effect of iron concentration on nickel metal removal in electroplating wastewater using an insulated electrolytic reactor double chamber electrodeposition cell (DCEC). The result of this study shows that any ratio variation of iron concentration to nickel gives varying impacts on nickel removal efficiency, electric current efficiency, and specific energy. On the fourth variation, the iron ratio of 1.29% removed 83.1% nickel (the highest removal efficiency) at the cost of 20.687 kWh / kg specific energy. The number is extremely high for energy needs. On the other hand, the variation of iron ratio of 1.73% consumpting only 15.067 kWh / kg, the lowest specific energy needs, resulted in the lowest removal efficiency of 63.6%.